2014
DOI: 10.2478/ffp-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biochemical properties in evaluation of forest soil quality

Abstract: The aim of this study was to assess the possibility of using biological and biochemical parameters in the evaluation of forest soil quality and changes caused by land use. The study attempted to determine a relationship between the enzymatic activity of soil, the number of earthworms and soil physico-chemical properties. The study was carried out in central Poland in adjoining Forest Districts (Przedbórz and Smardzewice). In soil samples taken from 12 research plots, basic physico-chemical properties, enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Yang et al (2006) investigated the combined effects of cadmium, zinc and lead on urease activities and concluded that urease is very sensitive to toxic concentrations of heavy metals. The highest urease activity was recorded under soil water pH 5.8 and the lowest activity at soil water pH 4.2 (Blonska and Lasota, 2014). The response of urease activity to drought, contamination and pH can be used to assess soil quality status.…”
Section: Factors Affecting Urease Activitymentioning
confidence: 99%
“…Yang et al (2006) investigated the combined effects of cadmium, zinc and lead on urease activities and concluded that urease is very sensitive to toxic concentrations of heavy metals. The highest urease activity was recorded under soil water pH 5.8 and the lowest activity at soil water pH 4.2 (Blonska and Lasota, 2014). The response of urease activity to drought, contamination and pH can be used to assess soil quality status.…”
Section: Factors Affecting Urease Activitymentioning
confidence: 99%
“…The subject literature shows that not many studies have been hitherto conducted on the soil enzymatic activity in the areas impacted by a natural disaster, such as a hurricane. Błońska and Lasota (2014) showed significantly lower dehydrogenase and urease activities in the wind-throw-affected areas, where the biological balance of the soil environment was disturbed. Kramer et al (2004) as well as Thürig et al (2005) demonstrated a decrease in the organic carbon during some decades after the wind-throw.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for its high heating value is that its carbon and hydrogen content (47% and 6%, respectively) are basically the same as that of Miscanthus ssp. and energy willow, but the nitrogen and ash content (0.2% and 1.8%, respectively), which reduce heating value, are much lower than their respective values [83]. Sida is very suitable for biogas production even with its greater moisture content, because its biogas yield is very high (cca.…”
Section: Theorymentioning
confidence: 99%
“…Sida is very suitable for biogas production even with its greater moisture content, because its biogas yield is very high (cca. 435 Ndm 3 kg -1 ODM) and its C/N ratio is very favourable [83].…”
Section: Theorymentioning
confidence: 99%